2019
DOI: 10.1021/acs.orglett.9b01954
|View full text |Cite
|
Sign up to set email alerts
|

Organophotoredox-Catalyzed C(sp2)–H Difluoromethylenephosphonation of Imidazoheterocycles

Abstract: A mild and efficient method for the direct difluoromethylenephosphonation of imidazopyridines has been developed using rose bengal (RB) as a photoredox catalyst. Bis(pinacolato)diboron (B 2 pin 2 ) is found to be a crucial additive in the present reaction. The present methodology is also applicable to other heterocycles like imidazo[2,1-b]thiazole, benzo [d]imidazo-[2,1-b]thiazole, and indole. The reaction possibly proceeds through a single electron transfer (SET) process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 63 publications
4
36
0
Order By: Relevance
“…From the optimization studies it was very much clear that 2-phenylimidazo[1,2-a]pyridine 1a decomposes in the absence of B2Pin2 and is necessary to get the desired product. From the above results and previous literature, 16,25 a plausible reaction mechanism was proposed for our reaction protocol (Scheme 4). In the presence of blue LED, rose bengal (RB) is converted to its excited state RB * which helps in generation of carbon radical species I from 2a.…”
Section: Methodssupporting
confidence: 64%
“…From the optimization studies it was very much clear that 2-phenylimidazo[1,2-a]pyridine 1a decomposes in the absence of B2Pin2 and is necessary to get the desired product. From the above results and previous literature, 16,25 a plausible reaction mechanism was proposed for our reaction protocol (Scheme 4). In the presence of blue LED, rose bengal (RB) is converted to its excited state RB * which helps in generation of carbon radical species I from 2a.…”
Section: Methodssupporting
confidence: 64%
“…The coupling product was not formed in the absence of B2pin2, suggesting that this additive stabilizes the imidazopyridine in the reaction medium. Based on these results, the authors in [37] proposed a reaction mechanism such as that shown in Scheme 7.…”
Section: Scheme 3 Selected Examples For the Difluoromethylation Reacmentioning
confidence: 99%
“…Singsardar, Hajra, and collaborators [37] have recently accomplished the difluoromethyl enephosphonation of imidazoheterocycles employing Rose Bengal (RB) as the photocatalyst, NaHCO 3 as the base, B 2 pin 2 as an additive in 1,4-dioxane as the solvent, and irradiated with blue LEDs, according to Scheme 6. The regioselectivity of the difluoromethylation reaction of coumarin derivatives is driven by the stability of the benzyl radical obtained as intermediate.…”
Section: Scheme 3 Selected Examples For the Difluoromethylation Reacmentioning
confidence: 99%
See 1 more Smart Citation
“…Hajra group reported a visible light-mediated difluoromethylenephosphonation of imidazo[1,2-a]pyridines 1 with BrCF 2 PO(OEt) 2 using rose bengal (RB) as photocatalyst, bis(pinacolato)diboron (B 2 pin 2 ) as an additive in 1,4-dioxane (Scheme 16). [34] A variety of imidazoheterocycles (1-3) bearing different functional groups reacted smoothly and produced the respective products 29 in 58-92% yields. Notably, indole derivatives also successfully produced corresponding C3 substituted products in 40-57% yields under similar conditions.…”
Section: C3-fluoroalkylationmentioning
confidence: 99%